2012
DOI: 10.1186/cc11333
|View full text |Cite
|
Sign up to set email alerts
|

Higher vs. lower fluid volume for septic shock: clinical characteristics and outcome in unselected patients in a prospective, multicenter cohort

Abstract: IntroductionPatients with septic shock require fluid, but the optimum amount is unknown. Therefore we assessed patient characteristics and outcome associated with fluid volume in unselected patients with septic shock including those with three days of shock.MethodsWe conducted a prospective, multicenter, observational study of all adult patients with septic shock during a 3-month study period at six general ICUs: three in university hospitals and three in regional hospitals. After day 1 and 3 of shock, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 21 publications
3
51
2
1
Order By: Relevance
“…Accordingly, our findings may not be generalizable beyond children ≤10 years of age with septic shock. Our findings in moderate to high risk patients are consistent with a recent study in adult patients with septic shock, which demonstrated no association between initial fluid status and mortality, although we did not replicate the association between higher fluid volumes and reduced mortality in patients with shock duration of three or more days (8). …”
Section: Discusssionsupporting
confidence: 84%
See 1 more Smart Citation
“…Accordingly, our findings may not be generalizable beyond children ≤10 years of age with septic shock. Our findings in moderate to high risk patients are consistent with a recent study in adult patients with septic shock, which demonstrated no association between initial fluid status and mortality, although we did not replicate the association between higher fluid volumes and reduced mortality in patients with shock duration of three or more days (8). …”
Section: Discusssionsupporting
confidence: 84%
“…Over 20 years ago, Carcillo and colleagues reported that in children with septic shock, fluid resuscitation in excess of 40 ml/kg within the first hour of presentation was associated with improved survival, without increased risk of cardiogenic pulmonary edema or acute respiratory distress syndrome (2). Since then, aggressive fluid resuscitation has been a core intervention for the management of both pediatric and adult septic shock (3, 4), and the practice has been supported by subsequent observational and interventional studies (5-8). …”
Section: Introductionmentioning
confidence: 99%
“…They also "assessed trends in the difference between actual and expected mortality in the low fluid range (1-5 L day one fluids) and the high fluid range (5-9+ L day one fluids)". The 5-L cut-off is interesting as it was defined by previously reported results [7] and confirmed very nicely by these authors. Day 1 fluid input averaged 4.4 L and was higher in patients who were ventilated and in shock than in patients without these diagnoses.…”
supporting
confidence: 73%
“…There is an emerging consensus in trauma management that avoidance of excessive non-blood product administration (i.e. synthetic colloid and crystalloid) around a strategy of damage control surgery improves outcome [170,171]; this has not been established in sepsis management where fluid volumes administered may be much higher, but the correct volume to administer remains ill-defined [172,173]. However, many workers have suggested benefit to prompt resuscitation following trauma and so 'permissive hypotension' and delayed resuscitation must be based around early surgical control to allow more complete resuscitation [174].…”
Section: Intravenous Fluid Therapy -Which Fluid and How Much?mentioning
confidence: 99%